Novel Multi Optical Trapping Tool Generation within Add/Drop Filter System Controlled by Light - Phichai Youplao; Somsak Mitatha; Preecha Yupapin (My University, 2011)
We propose a novel system of multi optical trapping tool using a bright soliton pulses propagating within the add/drop optical filter system. The multiplexing signals with different wavelengths of the bright solition are controlled and amplified within the system. The dynamic behavior of bright soliton interaction is analyzed and described. The signal is controlled and tuned to be an optical probe which can be configured as the multi optical tweezers. By using some suitable parameters, we found that the tweezers widths in add/drop at the drop ports are about 18 nm is achieved. Therefore, the generated multi optical tweezers can be amplified within the design system. In application, the optical tweezers train can be trapped light/atom, which can be transmitted and recovered by using the proposed system.
Keywords: Tweezers; Orbital Angular Momentum in Optics